PENERAPAN MODEL INQUIRY BASED LEARNING TERHADAP KEMAMPUAN MATHEMATICAL REASONING MAHASISWA - Audi Alexandra Zelliyanti; Yonisa Aisayah Fitri; Annisa Maulidiyah Rahmi Lestari; Netriwati; Dwi Lestari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the implementation of the Inquiry Based Learning model on students' mathematical reasoning abilities. The research employed a quantitative approach using a quasi-experimental method with a Pretest–Posttest Control Group Design. The sample consisted of 40 students, including 20 students in the experimental class and 20 students in the control class. Data were collected through a mathematical reasoning ability test and an inquiry questionnaire. The instrument testing results showed a Cronbach’s Alpha value of 0.979, indicating very high reliability, and all questionnaire items were declared valid because the Corrected Item-Total Correlation values were greater than 0.30. Descriptive statistical results showed that the average posttest score of the experimental class was 94.85, higher than that of the control class at 91.45. However, the independent sample t-test result showed a significance value of 0.229 > 0.05, indicating that there was no statistically significant difference between the two classes. Nevertheless, the Inquiry Based Learning model demonstrated a positive tendency in improving students’ mathematical reasoning abilities and encouraging active participation in the learning process.